Hot-melt fiber-based rigid filtering material and preparation method thereof

By using a combination of modified polyether ether ketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate in industrial wastewater filtration materials, it is solved that it is difficult to remove acid and alkali solutions, organic matter and heavy metal ions in industrial wastewater in the prior art. The problem is to achieve efficient filtration and pollution resistance of the material.

CN119386554AInactive Publication Date: 2025-02-07GUANGZHOU CHANNEL WORLD IND TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411562094.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat complex industrial wastewater, especially to remove acid and alkali solutions, organic matter and heavy metal ions.

Method used

After mixing modified polyether ether ketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate, a hot melt fiber-based rigid filter material was prepared by melt spinning and hot pressing film formation processes.

Benefits of technology

It improves the antibacterial properties of the material, the complexity of heavy metal ion and the adsorption properties of the material, and at the same time enhances the mechanical properties and pollution resistance of the material, effectively removing pollutants in industrial wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005118157450000031
    Figure BDA0005118157450000031
  • Figure BDA0005118157450000032
    Figure BDA0005118157450000032
  • Figure BDA0005118157450000041
    Figure BDA0005118157450000041
Patent Text Reader

Abstract

The invention discloses a hot-melt fiber-based rigid filter material and a preparation method thereof, and relates to the field of filter materials. When the hot-melt fiber-based rigid filter material is prepared, zinc oxide nanorods and silver nitrate are uniformly mixed and then react with 3-glycidyl ether oxypropyl trimethoxy silane, 2, 2 '-bipyridine methylamine and maleic anhydride in sequence to obtain functional silver-loaded zinc oxide nanorods; the preparation method comprises the following steps: reacting 4, 4 '-difluorobenzophenone, hydroquinone and 3, 3', 5, 5 '-tetramethyl biphenol, brominating, and grafting N-vinyl imidazole to obtain modified polyether-ether-ketone; and uniformly mixing the modified polyether-ether-ketone, the functional silver-loaded zinc oxide nanorod and ammonium persulfate, and carrying out melt spinning and hot-pressing film formation to prepare the hot-melt fiber-based rigid filter material. The prepared hot-melt fiber-based rigid filtering material has excellent mechanical property, heavy metal ion complexing property, antibacterial property and anion adsorbability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of filter materials, in particular to a hot-melt fiber-based rigid filter material and a preparation method thereof. Background Art

[0002] In recent years, the rapid consumption and waste of freshwater resources has become one of the most important issues in the field of environment that cannot be ignored. In the current situation of increasingly depleted water resources, in addition to inter-basin water transfer, collection of snow and ice meltwater, glacier meltwater, seawater desalination and other methods, humans are also constantly looking for new methods to achieve sustainable use of water resources. The total amount of water resources on the earth is limited, and today's freshwater resources are far from meeting people's growing living and production needs. Therefore, the most practical method today is to recycle sewage.

[0003] At present, industrial wastewater and domestic sewage are the two major sources of sewage on the earth. Due to the particularity of the chemical industry, the composition of industrial wastewater is complex and diverse, and often contains acid and alkali solutions, organic matter, heavy metal ions, etc., and these substances are often corrosive. Polyetheretherketone, as a special engineering plastic, has excellent chemical stability and high strength, and has incomparable advantages over other types of polymers in practical applications. It can not only resist immersion in acid, alkali and salt solutions, but also has good solvent resistance to many highly soluble organic solvents such as N, N-dimethylformamide. Therefore, the present invention prepares a hot-melt fiber-based rigid filter material with excellent properties. Summary of the invention

[0004] The object of the present invention is to provide a hot-melt fiber-based rigid filter material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention discloses a hot-melt fiber-based rigid filter material, which is prepared by melting, spinning and hot-pressing modified polyetheretherketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate and uniformly mixing them.

[0007] As an optimization, the modified polyetheretherketone is obtained by reacting 4,4'-difluorobenzophenone, hydroquinone and 3,3',5,5'-tetramethylbiphenol, followed by bromination and then grafting N-vinylimidazole.

[0008] As an optimization, the functionalized silver-loaded zinc oxide nanorods are obtained by mixing zinc oxide nanorods and silver nitrate, and then reacting with 3-glycidyloxypropyltrimethoxysilane, 2,2'-bipyrrolidonemethylamine, and maleic anhydride in sequence.

[0009] As an optimization, the zinc oxide nanorod model is 100 nm and comes from Guangzhou Hongwu Material Technology Co., Ltd.

[0010] A method for preparing a hot-melt fiber-based rigid filter material comprises the following preparation steps:

[0011] (1) Mixing zinc oxide nanorods, silver nitrate and anhydrous ethanol in a mass ratio of 1: (0.2-0.4): (14-16), stirring at 20-30° C. and 200-400 rpm for 3-5 hours, filtering, washing with deionized water for 3-5 times, and drying at 50-60° C. for 6-8 hours to obtain silver-loaded zinc oxide nanorods; mixing silver-loaded zinc oxide nanorods, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1: (4-6): (45-55), stirring at 65-75° C. and 300-400 rpm for 4-6 hours in a nitrogen atmosphere, naturally cooling to room temperature, filtering, washing with anhydrous ethanol and deionized water for 3-5 times, respectively, and drying at 55-65° C. for 11-13 hours to obtain pre-modified silver-loaded zinc oxide nanorods;

[0012] (2) Pre-modified silver-loaded zinc oxide nanorods, 2,2'-dipicolylamine and methanol were mixed in a mass ratio of 1:(2-3):(45-55), refluxed at 60-70°C for 5-7h, rotary evaporated at 65-75°C for 1-2h, washed with anhydrous ethanol for 3-5 times, and dried at 70-80°C for 6-8h to obtain modified silver-loaded zinc oxide nanorods; modified silver-loaded zinc oxide nanorods, maleic anhydride, p-hydroxyanisole, triethylamine and butanone were mixed in a mass ratio of 1:(3-4):(0.01-0.03):(0.01-0.02):(6-8), stirred at 75-85°C and 100-200 rpm for 5-7h, naturally cooled to room temperature, filtered, washed with deionized water and anhydrous ethanol for 3-5 times respectively, and dried at 55-65°C for 11-13h to obtain functionalized silver-loaded zinc oxide nanorods;

[0013] (3) 4,4'-difluorobenzophenone, hydroquinone, 3,3',5,5'-tetramethylbiphenol, anhydrous potassium carbonate, N,N-dimethylacetamide and toluene were mixed in a mass ratio of

[0014] 1:(0.2~0.3):(0.5~0.6):(0.94~0.96):(6~8):(4~5) Mix well, in nitrogen atmosphere, 145~155℃,

[0015] The mixture was stirred at 250-350 rpm for 1-3 h, heated to 165-175 ° C for prepolymerization for 55-65 min, heated to 195-205 ° C for continuous stirring for 2-4 h, poured into deionized water, allowed to stand until the precipitate mass remained unchanged, filtered, washed with deionized water and anhydrous ethanol for 3-5 times respectively, and dried at 75-85 ° C for 7-9 h to obtain methyl polyether ether ketone; methyl polyether ether ketone, N-bromosuccinimide, dibenzoyl peroxide and tetrachloroethane were mixed in a mass ratio of 1: (1.1-1.3): (0.07-0.09): (15-25), and dried in a nitrogen atmosphere at 80-90 ° C and 100-300 r pm, stirring for 4 to 6 hours, cooling naturally to room temperature, pouring into anhydrous ethanol and standing until the precipitate mass remains unchanged, filtering, Soxhlet extraction in acetone for 23 to 25 hours, drying at 65 to 75°C for 12 to 14 hours, and obtaining brominated polyetheretherketone; mixing brominated polyetheretherketone, N-vinylimidazole and N-methylpyrrolidone in a mass ratio of 1: (0.07 to 0.09): (10 to 20), stirring at 40 to 50°C and 100 to 200 rpm in a nitrogen atmosphere for 23 to 25 hours, standing at 75 to 85°C for 7 to 9 hours, washing with deionized water for 3 to 5 times, and drying at 55 to 65°C for 8 to 10 hours to obtain modified polyetheretherketone;

[0016] (4) The modified polyetheretherketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate are mixed in a mass ratio of 1:(0.03-0.05):(0.01-0.02), stirred at 245-255°C and 55-65 rpm for 10-20 min, extruded by a twin-screw extruder, bonded and cooled on a mesh curtain, hot-pressed at 15-25 MPa for 5-15 min, and allowed to stand at 75-85°C for 8-10 h to obtain a hot-melt fiber-based rigid filter material.

[0017] As an optimization, the reaction equation of the pre-modified silver-loaded zinc oxide nanorods in step (1) is:

[0018]

[0019] As an optimization, the reaction equation for modifying the silver-loaded zinc oxide nanorods in step (2) is:

[0020]

[0021] As an optimization, the reaction equation of the functionalized silver-loaded zinc oxide nanorods in step (2) is:

[0022]

[0023] As an optimization, the reaction equation of the methyl polyetheretherketone in step (3) is:

[0024]

[0025] As an optimization, the reaction equation for the brominated polyetheretherketone in step (3) is:

[0026]

[0027] As an optimization, the reaction equation of the modified polyetheretherketone in step (3) is:

[0028]

[0029] As an optimization, the extrusion spinning process conditions in step (4) are: fiber diameter 20 μm, stacking thickness 2 mm.

[0030] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0031] When preparing the hot-melt fiber-based rigid filter material, the present invention comprises the following steps: after zinc oxide nanorods and silver nitrate are uniformly mixed, the nanorods are sequentially reacted with 3-glycidyloxypropyltrimethoxysilane, 2,2'-bipyridylamine and maleic anhydride to obtain functionalized silver-loaded zinc oxide nanorods; after 4,4'-difluorobenzophenone, hydroquinone and 3,3',5,5'-tetramethylbiphenol are reacted and then brominated, and then N-vinyl imidazole is grafted to obtain modified polyetheretherketone; after the modified polyetheretherketone, the functionalized silver-loaded zinc oxide nanorods and ammonium persulfate are uniformly mixed, the nanorods are melt-spun and hot-pressed to form a film, and the hot-melt fiber-based rigid filter material is obtained.

[0032] First, zinc oxide nanorods and silver nitrate are mixed and then reacted with 3-glycidyloxypropyltrimethoxysilane, 2,2'-bipyrrolidone and maleic anhydride in sequence to obtain functionalized silver-loaded zinc oxide nanorods; by loading silver ions on zinc oxide nanorods, the growth of bacteria and other microorganisms can be inhibited, the charge characteristics of the membrane surface can be changed, the attachment of organic matter and particulate matter can be reduced, and the photocatalytic performance of zinc oxide can be promoted, thereby improving the antibacterial property of hot-melt fiber-based rigid filter materials; 2,2'-bipyrrolidone is grafted by reacting epoxy groups with secondary amines to form a stable five-membered ring complex structure with heavy metal ions, thereby improving the heavy metal ion complexing property of hot-melt fiber-based rigid filter materials; and maleic anhydride is grafted with hydroxyl groups produced by the reaction of epoxy groups with secondary amines to introduce double bonds and carboxyl structures, thereby participating in the cross-linking of the main chain while enhancing the hydrophilicity and reducing the deposition of dirt, thereby improving the mechanical properties and anti-fouling property of hot-melt fiber-based rigid filter materials.

[0033] Secondly, 4,4'-difluorobenzophenone, hydroquinone and 3,3',5,5'-tetramethylbiphenol are reacted and then brominated, and then grafted with N-vinyl imidazole to obtain modified polyetheretherketone; the modified polyetheretherketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate are mixed and then melt-spun and hot-pressed to form a film to obtain a hot-melt fiber-based rigid filter material; the methyl groups on the main chain of polyetheretherketone are brominated to introduce active sites that can react with imidazole for quaternary ammonium reaction to form imidazole quaternary ammonium salts, thereby changing the charge characteristics, attracting negatively charged pollutants, and improving the antibacterial and anion adsorption properties of the hot-melt fiber-based rigid filter material; at the same time, the double bond structure on N-vinyl imidazole can be cross-linked with the double bonds on the functionalized silver-loaded zinc oxide nanorods to improve the mechanical properties of the hot-melt fiber-based rigid filter material; ammonium persulfate is used as a thermal initiator to induce carbon-carbon double bond cross-linking while also generating ammonia gas, enriching the pore structure, and improving the filtration performance of the hot-melt fiber-based rigid filter material. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0035] Embodiment 1:

[0036] A method for preparing a hot-melt fiber-based rigid filter material, the method comprising the following preparation steps:

[0037] (1) Mix zinc oxide nanorods, silver nitrate and anhydrous ethanol in a mass ratio of 1:0.2:14, stir at 20°C and 200 rpm for 5 h, filter, wash with deionized water for 3 times, and dry at 50°C for 8 h to obtain silver-loaded zinc oxide nanorods; mix silver-loaded zinc oxide nanorods, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1:4:45, stir at 65°C and 300 rpm for 6 h in a nitrogen atmosphere, cool naturally to room temperature, filter, wash with anhydrous ethanol and deionized water for 3 times, respectively, and dry at 55°C for 13 h to obtain pre-modified silver-loaded zinc oxide nanorods;

[0038] (2) Pre-modified silver-loaded zinc oxide nanorods, 2,2'-dipicolylamine and methanol were mixed in a mass ratio of 1:2:45, refluxed at 60°C for 7h, rotary evaporated at 65°C for 2h, washed with anhydrous ethanol for 3 times, and dried at 70°C for 8h to obtain modified silver-loaded zinc oxide nanorods; modified silver-loaded zinc oxide nanorods, maleic anhydride, p-hydroxyanisole, triethylamine and butanone were mixed in a mass ratio of 1:3:0.01:0.01:6, stirred at 75°C and 100 rpm for 7h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 3 times respectively, and dried at 55°C for 13h to obtain functionalized silver-loaded zinc oxide nanorods;

[0039] (3) 4,4'-difluorobenzophenone, hydroquinone, 3,3',5,5'-tetramethylbiphenol, anhydrous potassium carbonate, N,N-dimethylacetamide and toluene were mixed in a mass ratio of 1:0.2:0.5:0.94:6:4, stirred at 145°C and 250rpm for 3h in a nitrogen atmosphere, heated to 165°C for prepolymerization for 65min, heated to 195°C and continued to stir for 4h, poured into deionized water, allowed to stand until the precipitate mass remained unchanged, filtered, washed with deionized water and anhydrous ethanol for 3 times respectively, and dried at 75°C for 9h to obtain methyl polyetheretherketone; methyl polyetheretherketone, N-bromosuccinimide, peroxide Dibenzoyl chloride and tetrachloroethane are mixed in a mass ratio of 1:1.1:0.07:15, stirred at 80°C and 100rpm for 6h in a nitrogen atmosphere, cooled naturally to room temperature, poured into anhydrous ethanol and allowed to stand until the precipitate mass remains unchanged, filtered, extracted with acetone for 23h, and dried at 65°C for 14h to obtain brominated polyetheretherketone; brominated polyetheretherketone, N-vinylimidazole and N-methylpyrrolidone are mixed in a mass ratio of 1:0.07:10, stirred at 40°C and 100rpm for 25h in a nitrogen atmosphere, allowed to stand at 75°C for 9h, washed with deionized water 3 times, and dried at 55°C for 10h to obtain modified polyetheretherketone;

[0040] (4) The modified polyetheretherketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate were mixed in a mass ratio of 1:0.03:0.01, stirred at 245°C and 55 rpm for 20 min, extruded by a twin-screw extruder, bonded and cooled on a mesh curtain, hot-pressed at 15 MPa for 15 min, and allowed to stand at 75°C for 10 h to obtain a hot-melt fiber-based rigid filter material.

[0041] Embodiment 2:

[0042] A method for preparing a hot-melt fiber-based rigid filter material, the method comprising the following preparation steps:

[0043] (1) Mix zinc oxide nanorods, silver nitrate and anhydrous ethanol in a mass ratio of 1:0.3:15, stir at 25°C and 300 rpm for 4 hours, filter, wash with deionized water 4 times, and dry at 55°C for 7 hours to obtain silver-loaded zinc oxide nanorods; mix silver-loaded zinc oxide nanorods, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1:5:50, stir at 70°C and 350 rpm for 5 hours in a nitrogen atmosphere, cool naturally to room temperature, filter, wash with anhydrous ethanol and deionized water 4 times respectively, and dry at 60°C for 12 hours to obtain pre-modified silver-loaded zinc oxide nanorods;

[0044] (2) Pre-modified silver-loaded zinc oxide nanorods, 2,2'-dipicolylamine and methanol were mixed in a mass ratio of 1:2.5:50, refluxed at 65°C for 6 h, rotary evaporated at 70°C for 1.5 h, washed with anhydrous ethanol 4 times, and dried at 75°C for 7 h to obtain modified silver-loaded zinc oxide nanorods; modified silver-loaded zinc oxide nanorods, maleic anhydride, p-hydroxyanisole, triethylamine and butanone were mixed in a mass ratio of 1:3.5:0.02:0.015:7, stirred at 80°C and 150 rpm for 6 h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol 4 times respectively, and dried at 60°C for 12 h to obtain functionalized silver-loaded zinc oxide nanorods;

[0045] (3) 4,4'-difluorobenzophenone, hydroquinone, 3,3',5,5'-tetramethylbiphenol, anhydrous potassium carbonate, N,N-dimethylacetamide and toluene were mixed in a mass ratio of 1:0.25:0.55:0.95:7:4.5, stirred at 150°C and 300 rpm for 2 h in a nitrogen atmosphere, heated to 170°C for prepolymerization for 60 min, heated to 200°C and continued to stir for 3 h, poured into deionized water, allowed to stand until the precipitate mass remained unchanged, filtered, washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 80°C for 8 h to obtain methyl polyetheretherketone; methyl polyetheretherketone, N-bromosuccinimide, Dibenzoyl peroxide and tetrachloroethane are mixed in a mass ratio of 1:1.2:0.08:20, stirred at 85°C and 200rpm for 5h in a nitrogen atmosphere, cooled naturally to room temperature, poured into anhydrous ethanol and allowed to stand until the precipitate mass remains unchanged, filtered, extracted with acetone for 24h, and dried at 70°C for 13h to obtain brominated polyetheretherketone; brominated polyetheretherketone, N-vinylimidazole and N-methylpyrrolidone are mixed in a mass ratio of 1:0.08:15, stirred at 45°C and 150rpm in a nitrogen atmosphere for 24h, allowed to stand at 80°C for 8h, washed with deionized water 4 times, and dried at 60°C for 9h to obtain modified polyetheretherketone;

[0046] (4) The modified polyetheretherketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate were mixed in a mass ratio of 1:0.04:0.015, stirred at 250°C and 60 rpm for 15 min, extruded by a twin-screw extruder, bonded and cooled on a mesh curtain, hot-pressed at 20 MPa for 10 min, and allowed to stand at 80°C for 9 h to obtain a hot-melt fiber-based rigid filter material.

[0047] Embodiment 3:

[0048] A method for preparing a hot-melt fiber-based rigid filter material, the method comprising the following preparation steps:

[0049] (1) Mixing zinc oxide nanorods, silver nitrate and anhydrous ethanol in a mass ratio of 1:0.4:16, stirring at 30°C and 400 rpm for 3 h, filtering, washing with deionized water for 5 times, and drying at 60°C for 6 h to obtain silver-loaded zinc oxide nanorods; mixing silver-loaded zinc oxide nanorods, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1:6:55, stirring at 75°C and 400 rpm for 4 h in a nitrogen atmosphere, naturally cooling to room temperature, filtering, washing with anhydrous ethanol and deionized water for 5 times respectively, and drying at 65°C for 11 h to obtain pre-modified silver-loaded zinc oxide nanorods;

[0050] (2) Pre-modified silver-loaded zinc oxide nanorods, 2,2'-dipicolylamine and methanol were mixed in a mass ratio of 1:3:55, refluxed at 70°C for 5 h, rotary evaporated at 75°C for 1 h, washed with anhydrous ethanol 5 times, and dried at 80°C for 6 h to obtain modified silver-loaded zinc oxide nanorods; modified silver-loaded zinc oxide nanorods, maleic anhydride, p-hydroxyanisole, triethylamine and butanone were mixed in a mass ratio of 1:4:0.03:0.02:8, stirred at 85°C and 200 rpm for 5 h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol 5 times respectively, and dried at 65°C for 11 h to obtain functionalized silver-loaded zinc oxide nanorods;

[0051] (3) 4,4'-difluorobenzophenone, hydroquinone, 3,3',5,5'-tetramethylbiphenol, anhydrous potassium carbonate, N,N-dimethylacetamide and toluene were mixed in a mass ratio of 1:0.3:0.6:0.96:8:5, stirred at 155°C and 350rpm for 1h in a nitrogen atmosphere, heated to 175°C for prepolymerization for 55min, heated to 205°C and stirred for 2h, poured into deionized water, allowed to stand until the precipitate mass remained unchanged, filtered, washed with deionized water and anhydrous ethanol for 5 times respectively, and dried at 85°C for 7h to obtain methyl polyetheretherketone; methyl polyetheretherketone, N-bromosuccinimide, peroxide Dibenzoyl chloride and tetrachloroethane are mixed in a mass ratio of 1:1.3:0.09:25, stirred at 90°C and 300rpm for 4h in a nitrogen atmosphere, cooled naturally to room temperature, poured into anhydrous ethanol and allowed to stand until the precipitate mass remains unchanged, filtered, extracted with acetone for 25h, and dried at 75°C for 12h to obtain brominated polyetheretherketone; brominated polyetheretherketone, N-vinylimidazole and N-methylpyrrolidone are mixed in a mass ratio of 1:0.09:20, stirred at 50°C and 200rpm in a nitrogen atmosphere for 23h, allowed to stand at 85°C for 7h, washed with deionized water 5 times, and dried at 65°C for 8h to obtain modified polyetheretherketone;

[0052] (4) The modified polyetheretherketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate were mixed in a mass ratio of 1:0.05:0.02, stirred at 255°C and 65 rpm for 10 min, extruded by a twin-screw extruder, bonded and cooled on a mesh curtain, hot-pressed at 25 MPa for 5 min, and allowed to stand at 85°C for 8 h to obtain a hot-melt fiber-based rigid filter material.

[0053] Comparative Example 1:

[0054] A method for preparing a hot-melt fiber-based rigid filter material, the method comprising the following preparation steps:

[0055] (1) Mix zinc oxide nanorods, silver nitrate and anhydrous ethanol in a mass ratio of 1:0.3:15, stir at 25°C and 300 rpm for 4 hours, filter, wash with deionized water 4 times, and dry at 55°C for 7 hours to obtain silver-loaded zinc oxide nanorods; mix silver-loaded zinc oxide nanorods, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1:5:50, stir at 70°C and 350 rpm for 5 hours in a nitrogen atmosphere, cool naturally to room temperature, filter, wash with anhydrous ethanol and deionized water 4 times respectively, and dry at 60°C for 12 hours to obtain pre-modified silver-loaded zinc oxide nanorods;

[0056] (2) pre-modified silver-loaded zinc oxide nanorods, 2,2'-dipicolylamine and methanol were mixed in a mass ratio of 1:2.5:50, refluxed at 65°C for 6 h, rotary evaporated at 70°C for 1.5 h, washed with anhydrous ethanol 4 times, and dried at 75°C for 7 h to obtain modified silver-loaded zinc oxide nanorods;

[0057] (3) 4,4'-difluorobenzophenone, hydroquinone, 3,3',5,5'-tetramethylbiphenol, anhydrous potassium carbonate, N,N-dimethylacetamide and toluene were mixed in a mass ratio of 1:0.25:0.55:0.95:7:4.5, stirred at 150°C and 300 rpm for 2 h in a nitrogen atmosphere, heated to 170°C for prepolymerization for 60 min, heated to 200°C and continued to stir for 3 h, poured into deionized water, allowed to stand until the precipitate mass remained unchanged, filtered, washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 80°C for 8 h to obtain methyl polyetheretherketone; methyl polyetheretherketone, N-bromosuccinimide, Dibenzoyl peroxide and tetrachloroethane are mixed in a mass ratio of 1:1.2:0.08:20, stirred at 85°C and 200rpm for 5h in a nitrogen atmosphere, cooled naturally to room temperature, poured into anhydrous ethanol and allowed to stand until the precipitate mass remains unchanged, filtered, extracted with acetone for 24h, and dried at 70°C for 13h to obtain brominated polyetheretherketone; brominated polyetheretherketone, N-vinylimidazole and N-methylpyrrolidone are mixed in a mass ratio of 1:0.08:15, stirred at 45°C and 150rpm in a nitrogen atmosphere for 24h, allowed to stand at 80°C for 8h, washed with deionized water 4 times, and dried at 60°C for 9h to obtain modified polyetheretherketone;

[0058] (4) The modified polyetheretherketone, modified silver-loaded zinc oxide nanorods and ammonium persulfate were mixed in a mass ratio of 1:0.04:0.015, stirred at 250°C and 60 rpm for 15 min, extruded by a twin-screw extruder, bonded and cooled on a mesh curtain, hot-pressed at 20 MPa for 10 min, and allowed to stand at 80°C for 9 h to obtain a hot-melt fiber-based rigid filter material.

[0059] Comparative Example 2:

[0060] A method for preparing a hot-melt fiber-based rigid filter material, the method comprising the following preparation steps:

[0061] (1) Mixing zinc oxide nanorods, silver nitrate and anhydrous ethanol in a mass ratio of 1:0.3:15, stirring at 25°C and 300 rpm for 4 hours, filtering, washing with deionized water for 4 times, and drying at 55°C for 7 hours to obtain silver-loaded zinc oxide nanorods; mixing silver-loaded zinc oxide nanorods, hydroxymethyltriethoxysilane and anhydrous ethanol in a mass ratio of 1:5:50, stirring at 70°C and 350 rpm for 5 hours in a nitrogen atmosphere, naturally cooling to room temperature, filtering, washing with anhydrous ethanol and deionized water for 4 times, respectively, and drying at 60°C for 12 hours to obtain pre-modified silver-loaded zinc oxide nanorods;

[0062] (2) pre-modified silver-loaded zinc oxide nanorods, maleic anhydride, p-hydroxyanisole, triethylamine and butanone were mixed in a mass ratio of 1:3.5:0.02:0.015:7, stirred at 80°C and 150 rpm for 6 h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 60°C for 12 h to obtain functionalized silver-loaded zinc oxide nanorods;

[0063] (3) 4,4'-difluorobenzophenone, hydroquinone, 3,3',5,5'-tetramethylbiphenol, anhydrous potassium carbonate, N,N-dimethylacetamide and toluene were mixed in a mass ratio of 1:0.25:0.55:0.95:7:4.5, stirred at 150°C and 300 rpm for 2 h in a nitrogen atmosphere, heated to 170°C for prepolymerization for 60 min, heated to 200°C and continued to stir for 3 h, poured into deionized water, allowed to stand until the precipitate mass remained unchanged, filtered, washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 80°C for 8 h to obtain methyl polyetheretherketone; methyl polyetheretherketone, N-bromosuccinimide, Dibenzoyl peroxide and tetrachloroethane are mixed in a mass ratio of 1:1.2:0.08:20, stirred at 85°C and 200rpm for 5h in a nitrogen atmosphere, cooled naturally to room temperature, poured into anhydrous ethanol and allowed to stand until the precipitate mass remains unchanged, filtered, extracted with acetone for 24h, and dried at 70°C for 13h to obtain brominated polyetheretherketone; brominated polyetheretherketone, N-vinylimidazole and N-methylpyrrolidone are mixed in a mass ratio of 1:0.08:15, stirred at 45°C and 150rpm in a nitrogen atmosphere for 24h, allowed to stand at 80°C for 8h, washed with deionized water 4 times, and dried at 60°C for 9h to obtain modified polyetheretherketone;

[0064] (4) The modified polyetheretherketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate were mixed in a mass ratio of 1:0.04:0.015, stirred at 250°C and 60 rpm for 15 min, extruded by a twin-screw extruder, bonded and cooled on a mesh curtain, hot-pressed at 20 MPa for 10 min, and allowed to stand at 80°C for 9 h to obtain a hot-melt fiber-based rigid filter material.

[0065] Comparative Example 3:

[0066] A method for preparing a hot-melt fiber-based rigid filter material, the method comprising the following preparation steps:

[0067] (1) zinc oxide nanorods, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:5:50, stirred at 70°C and 350 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature and then filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 60°C for 12 h to obtain pre-modified silver-loaded zinc oxide nanorods;

[0068] (2) Pre-modified silver-loaded zinc oxide nanorods, 2,2'-dipicolylamine and methanol were mixed in a mass ratio of 1:2.5:50, refluxed at 65°C for 6 h, rotary evaporated at 70°C for 1.5 h, washed with anhydrous ethanol 4 times, and dried at 75°C for 7 h to obtain modified silver-loaded zinc oxide nanorods; modified silver-loaded zinc oxide nanorods, maleic anhydride, p-hydroxyanisole, triethylamine and butanone were mixed in a mass ratio of 1:3.5:0.02:0.015:7, stirred at 80°C and 150 rpm for 6 h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol 4 times respectively, and dried at 60°C for 12 h to obtain functionalized silver-loaded zinc oxide nanorods;

[0069] (3) 4,4'-difluorobenzophenone, hydroquinone, 3,3',5,5'-tetramethylbiphenol, anhydrous potassium carbonate, N,N-dimethylacetamide and toluene were mixed in a mass ratio of 1:0.25:0.55:0.95:7:4.5, stirred at 150°C and 300 rpm for 2 h in a nitrogen atmosphere, heated to 170°C for prepolymerization for 60 min, heated to 200°C and continued to stir for 3 h, poured into deionized water, allowed to stand until the precipitate mass remained unchanged, filtered, washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 80°C for 8 h to obtain methyl polyetheretherketone; methyl polyetheretherketone, N-bromosuccinimide, Dibenzoyl peroxide and tetrachloroethane are mixed in a mass ratio of 1:1.2:0.08:20, stirred at 85°C and 200rpm for 5h in a nitrogen atmosphere, cooled naturally to room temperature, poured into anhydrous ethanol and allowed to stand until the precipitate mass remains unchanged, filtered, extracted with acetone for 24h, and dried at 70°C for 13h to obtain brominated polyetheretherketone; brominated polyetheretherketone, N-vinylimidazole and N-methylpyrrolidone are mixed in a mass ratio of 1:0.08:15, stirred at 45°C and 150rpm in a nitrogen atmosphere for 24h, allowed to stand at 80°C for 8h, washed with deionized water 4 times, and dried at 60°C for 9h to obtain modified polyetheretherketone;

[0070] (4) The modified polyetheretherketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate were mixed in a mass ratio of 1:0.04:0.015, stirred at 250°C and 60 rpm for 15 min, extruded by a twin-screw extruder, bonded and cooled on a mesh curtain, hot-pressed at 20 MPa for 10 min, and allowed to stand at 80°C for 9 h to obtain a hot-melt fiber-based rigid filter material.

[0071] Comparative Example 4:

[0072] A method for preparing a hot-melt fiber-based rigid filter material, the method comprising the following preparation steps:

[0073] (1) Mix zinc oxide nanorods, silver nitrate and anhydrous ethanol in a mass ratio of 1:0.3:15, stir at 25°C and 300 rpm for 4 hours, filter, wash with deionized water 4 times, and dry at 55°C for 7 hours to obtain silver-loaded zinc oxide nanorods; mix silver-loaded zinc oxide nanorods, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1:5:50, stir at 70°C and 350 rpm for 5 hours in a nitrogen atmosphere, cool naturally to room temperature, filter, wash with anhydrous ethanol and deionized water 4 times respectively, and dry at 60°C for 12 hours to obtain pre-modified silver-loaded zinc oxide nanorods;

[0074] (2) Pre-modified silver-loaded zinc oxide nanorods, 2,2'-dipicolylamine and methanol were mixed in a mass ratio of 1:2.5:50, refluxed at 65°C for 6 h, rotary evaporated at 70°C for 1.5 h, washed with anhydrous ethanol 4 times, and dried at 75°C for 7 h to obtain modified silver-loaded zinc oxide nanorods; modified silver-loaded zinc oxide nanorods, maleic anhydride, p-hydroxyanisole, triethylamine and butanone were mixed in a mass ratio of 1:3.5:0.02:0.015:7, stirred at 80°C and 150 rpm for 6 h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol 4 times respectively, and dried at 60°C for 12 h to obtain functionalized silver-loaded zinc oxide nanorods;

[0075] (3) 4,4'-difluorobenzophenone, hydroquinone, 3,3',5,5'-tetramethylbiphenol, anhydrous potassium carbonate, N,N-dimethylacetamide and toluene were mixed in a mass ratio of 1:0.25:0.55:0.95:7:4.5, stirred at 150°C and 300 rpm for 2 h in a nitrogen atmosphere, heated to 170°C for prepolymerization for 60 min, heated to 200°C and continued to stir for 3 h, poured into deionized water, allowed to stand until the precipitate mass remained unchanged, filtered, and filtered with deionized water. The mixture was washed with water and anhydrous ethanol for 4 times, and dried at 80°C for 8h to obtain methyl polyetheretherketone; methyl polyetheretherketone, N-bromosuccinimide, dibenzoyl peroxide and tetrachloroethane were mixed in a mass ratio of 1:1.2:0.08:20, stirred at 85°C and 200rpm for 5h in a nitrogen atmosphere, cooled naturally to room temperature, poured into anhydrous ethanol and allowed to stand until the mass of the precipitate remained unchanged, then filtered, extracted with acetone for 24h, and dried at 70°C for 13h to obtain brominated polyetheretherketone;

[0076] (4) Brominated polyetheretherketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate were mixed in a mass ratio of 1:0.04:0.015, stirred at 250°C and 60 rpm for 15 min, extruded by a twin-screw extruder, bonded and cooled on a mesh curtain, hot-pressed at 20 MPa for 10 min, and allowed to stand at 80°C for 9 h to obtain a hot-melt fiber-based rigid filter material.

[0077] Test Case

[0078] 1. Heavy metal ion complexation

[0079] Test method: The hot-melt fiber-based rigid filter material obtained in each embodiment and the comparative example are of the same size and tested at 24°C, 0.1 MPa, Pb 2+ The ion concentration was 100 mg / L (C0) and the Pb content in the filtrate was tested by UV spectrophotometer. 2+ Ion concentration C1, calculated complexation rate = (C0-C1) / C0*100%.

[0080] 2. Anion adsorption

[0081] Test method: Take samples of the same size as the hot-melt fiber-based rigid filter material obtained in each embodiment and the comparative example, prepare 100 ml of a Congo red solution with a concentration of 100 mg / L (C0), drain it into a filtration device with a glass rod, filter it under a transmembrane air pressure of 0.4 bar, test the Congo red concentration C1 in the filtrate, and calculate the adsorption rate = (C0-C1) / C0*100%.

[0082] 3. Antibacterial

[0083] Test method: Take the hot-melt fiber-based rigid filter material obtained in each embodiment and the control example of the same size, disinfect it under ultraviolet light for 12 hours as the test sample, put the samples into the liquid culture medium with the inoculated concentration of Escherichia coli solution and continue to culture for 12 hours, take 10 μL of the cultured bacterial solution and inoculate it into a solid culture dish containing agar, continue to culture at 37°C for 24 hours, count the number of surviving bacteria N1 (no sample is added as the control group to count the number of surviving bacteria N0), and calculate the antibacterial rate = (N0-N1) / N0*100%.

[0084] 4. Mechanical properties

[0085] Test method: The hot-melt fiber-based rigid filter materials obtained in each embodiment and the comparative example were cut into dumbbell-shaped strips of 20 mm × 5 mm in size, and the breaking strength was tested using a LLY-06F universal tensile tester at 20°C, 50% humidity, and a tensile speed of 20 mm / min.

[0086] Table 1 below shows the analysis results of the mechanical properties, heavy metal ion complexing properties, antibacterial properties and anion adsorption properties of the hot-melt fiber-based rigid filter materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0087] Table 1

[0088] Complexation rate % Adsorption rate % Antibacterial rate% Breaking strength MPa Example 1 98.4 99.38 98.8 49.7 Example 2 98.7 99.41 99.6 49.9 Example 3 98.2 99.32 98.4 49.4 Comparative Example 1 92.8 99.26 97.3 21.2 Comparative Example 2 32.5 99.18 98.1 48.6 Comparative Example 3 97.4 90.54 43.7 47.8 Comparative Example 4 93.1 47.83 29.5 16.3

[0089] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the hot-melt fiber-based rigid filter material prepared in the present invention has good mechanical properties, heavy metal ion complexing properties, antibacterial properties and anion adsorption properties.

[0090] By comparison, the breaking strength of Examples 1, 2, and 3 is higher than that of Comparative Example 1, which illustrates that the hydroxy-grafted maleic anhydride produced by the reaction of epoxy groups with secondary amines introduces double bonds and carboxyl structures, participates in main chain crosslinking, and improves the mechanical properties of hot-melt fiber-based rigid filter materials.

[0091] By comparison, the complexation rates of Examples 1, 2, and 3 are higher than those of Comparative Example 2, indicating that the complexation of heavy metal ions of hot-melt fiber-based rigid filter materials is improved by reacting epoxy groups with secondary amines to graft 2,2'-dipicolylamine to form a stable five-membered ring complex structure with heavy metal ions.

[0092] By comparison, the antibacterial rates of Examples 1, 2, and 3 are higher than those of Comparative Example 3, which shows that by loading silver ions on zinc oxide nanorods, the growth of bacteria and other microorganisms can be inhibited, the charge characteristics of the membrane surface can be changed, the adhesion of organic matter and particulate matter can be reduced, and the photocatalytic performance of zinc oxide can be promoted, thereby improving the antibacterial properties of hot-melt fiber-based rigid filter materials.

[0093] By comparison, the adsorption rate, antibacterial rate and breaking strength of Examples 1, 2 and 3 are higher than those of Comparative Example 4, which shows that by brominating the methyl on the main chain of polyetheretherketone, an active site that can undergo quaternary ammonium reaction with imidazole is introduced to form imidazole quaternary ammonium salt, thereby changing the charge characteristics, attracting negatively charged pollutants, and improving the antibacterial and anion adsorption properties of the hot-melt fiber-based rigid filter material; at the same time, the double bond structure on N-vinylimidazole can be cross-linked with the double bonds on the functionalized silver-loaded zinc oxide nanorods, thereby improving the mechanical properties of the hot-melt fiber-based rigid filter material.

[0094] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A hot-melt fiber-based rigid filter material, characterized in that: The hot-melt fiber-based rigid filter material is prepared by mixing modified polyetheretherketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate, and then melt-spinning and hot-pressing to form a film; The modified polyetheretherketone is obtained by reacting 4,4'-difluorobenzophenone, hydroquinone and 3,3',5,5'-tetramethylbiphenol, followed by bromination and then grafting N-vinylimidazole. The functionalized silver-loaded zinc oxide nanorods are obtained by mixing zinc oxide nanorods and silver nitrate, and then reacting with 3-glycidyloxypropyltrimethoxysilane, 2,2'-bipyridinemethylamine and maleic anhydride in sequence.

2. A method for preparing a hot-melt fiber-based rigid filter material, characterized in that: The method comprises the following preparation steps: (1) Mixing zinc oxide nanorods, silver nitrate and anhydrous ethanol in a mass ratio of 1: (0.2-0.4): (14-16), stirring at 20-30° C. and 200-400 rpm for 3-5 hours, filtering, washing with deionized water for 3-5 times, and drying at 50-60° C. for 6-8 hours to obtain silver-loaded zinc oxide nanorods; mixing silver-loaded zinc oxide nanorods, 3-glycidyloxypropyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1: (4-6): (45-55), stirring at 65-75° C. and 300-400 rpm for 4-6 hours in a nitrogen atmosphere, naturally cooling to room temperature, filtering, washing with anhydrous ethanol and deionized water for 3-5 times, respectively, and drying at 55-65° C. for 11-13 hours to obtain pre-modified silver-loaded zinc oxide nanorods; (2) Pre-modified silver-loaded zinc oxide nanorods, 2,2'-dipicolylamine and methanol were mixed in a mass ratio of 1:(2-3):(45-55), refluxed at 60-70°C for 5-7h, rotary evaporated at 65-75°C for 1-2h, washed with anhydrous ethanol for 3-5 times, and dried at 70-80°C for 6-8h to obtain modified silver-loaded zinc oxide nanorods; modified silver-loaded zinc oxide nanorods, maleic anhydride, p-hydroxyanisole, triethylamine and butanone were mixed in a mass ratio of 1:(3-4):(0.01-0.03):(0.01-0.02):(6-8), stirred at 75-85°C and 100-200 rpm for 5-7h, naturally cooled to room temperature, filtered, washed with deionized water and anhydrous ethanol for 3-5 times respectively, and dried at 55-65°C for 11-13h to obtain functionalized silver-loaded zinc oxide nanorods; (3) 4,4'-difluorobenzophenone, hydroquinone, 3,3',5,5'-tetramethylbiphenol, anhydrous potassium carbonate, N,N-dimethylacetamide and toluene were mixed in a mass ratio of 1:(0.2-0.3):(0.5-0.6):(0.94-0.96):(6-8):(4-5) mix well, stir at 145-155°C and 250-350rpm in a nitrogen atmosphere for 1-3h, heat to 165-175°C for prepolymerization for 55-65min, heat to 195-205°C and continue stirring for 2-4h, pour into deionized water, let stand until the precipitate mass remains unchanged, filter, wash with deionized water and anhydrous ethanol for 3-5 times respectively, dry at 75-85°C for 7-9h to obtain methyl polyether ether ketone; methyl polyether ether ketone, N-bromosuccinimide, dibenzoyl peroxide and tetrachloroethane in a mass ratio 1:(1.1-1.3):(0.07-0.09):(15-25) are mixed, stirred at 80-90°C and 100-300rpm for 4-6h in a nitrogen atmosphere, cooled naturally to room temperature, poured into anhydrous ethanol and allowed to stand until the precipitate mass remains unchanged, filtered, extracted with acetone for 23-25h by Soxhlet, dried at 65-75°C for 12-14h, and brominated polyetheretherketone is obtained; brominated polyetheretherketone, N-vinylimidazole and N-methylpyrrolidone are mixed at a mass ratio of 1:(0.07-0.09):(10-20), stirred at 40-50°C and 100-200rpm for 23-25h in a nitrogen atmosphere, allowed to stand at 75-85°C for 7-9h, washed with deionized water for 3-5 times, dried at 55-65°C for 8-10h, and modified polyetheretherketone is obtained; (4) The modified polyetheretherketone, functionalized silver-loaded zinc oxide nanorods and ammonium persulfate are mixed in a mass ratio of 1:(0.03-0.05):(0.01-0.02), stirred at 245-255°C and 55-65 rpm for 10-20 min, extruded by a twin-screw extruder, bonded and cooled on a mesh curtain, hot-pressed at 15-25 MPa for 5-15 min, and allowed to stand at 75-85°C for 8-10 h to obtain a hot-melt fiber-based rigid filter material.

3. The method for preparing a hot-melt fiber-based rigid filter material according to claim 2, characterized in that: The reaction equation of the pre-modified silver-loaded zinc oxide nanorods in step (1) is:

4. The method for preparing a hot-melt fiber-based rigid filter material according to claim 2, characterized in that: The reaction equation for the modified silver-loaded zinc oxide nanorods in step (2) is:

5. The method for preparing a hot-melt fiber-based rigid filter material according to claim 2, characterized in that: The reaction equation of the functionalized silver-loaded zinc oxide nanorods in step (2) is:

6. The method for preparing a hot-melt fiber-based rigid filter material according to claim 2, characterized in that: The reaction equation of the methyl polyetheretherketone in step (3) is:

7. The method for preparing a hot-melt fiber-based rigid filter material according to claim 2, characterized in that: The reaction equation of the brominated polyetheretherketone in step (3) is:

8. The method for preparing a hot-melt fiber-based rigid filter material according to claim 2, characterized in that: The reaction equation of the modified polyetheretherketone in step (3) is:

9. The method for preparing a hot-melt fiber-based rigid filter material according to claim 2, characterized in that: The extrusion spinning process conditions in step (4) are: fiber diameter 20 μm, stacking thickness 2 mm.